The prevalence and symptoms characteristic of functional constipation using Rome III diagnostic criteria among tertiary education students - Lim, Ying Jye; Jamaluddin, Rosita; Chieng, Jin Yu; Hazizi, Abu Saad (Public Library of Science, 2016)
Background and Aims Functional constipation is very common with heterogeneous symptoms that have substantial impact on patient quality of life as well as medical resources which are rarely reported as life-threatening. The aim of this study is to examine the prevalence and symptoms characteristic of functional constipation (FC) by using Rome III diagnostic criteria among tertiary education students with an intention to introduce treatment in the future.